Ação social e terceiro setor no Brasil - Oliveira, Sidney Benedito de (2005)
This research work, has the purpose to analyze the social importance of the Third Sector in Brazil and identify, which is the representative of Non-profit Institutions to offer jobs in social assistance, education, health, culture and recreation. We saw this, since the beginnings of the social action, as well as its historical antecedents, showing the social politics adopted in Brazil until the 1988 Constitution and culminating with the legal mark and the legislation for the Third Sector. We also consider about the Third Sector institutionalization, presenting the concepts and characteristics that guides it: the interaction of civil society and citizenship and the importance of local power, for the decentralization of resources, indicating the municipality as the place for the social articulations. We show a strategic point of view about the Companies Social Responsibilities, concerning to Non-profit Institutions and the use of social marketing as a management instrument to introduce a corporative philanthropy. The research conduct us to analyze the representative of Non-profit Institutions with regard to the totality of companies included in the Companies Central Register CEMPRE _ IBGE over 2002 year, according to the number of persons with a salaried employee, and finally does recommendations about new researches to indicate some ways and means that will contribute to improve the analyses of the Brazilians Third Sector